A two-photon fluorescent probe for detecting lipid droplet viscosity in living cells and zebra fish. (7th November 2018) - Peng, Min; Yin, Junling; Lin, Weiying
Abstract : A fluorescent probe CBA with high photostability to measure the viscosity changes of lipid drops. Abstract : The detection of lipid droplet (LD) viscosity is very important for clinical research. Herein, we described a new two-photon fluorescent probe CBA for sensing the viscosity changes of LDs. Using this powerful probe, monitoring the viscosity variations has been achieved not only in cells but also in zebra fish.